Pygopus2 ameliorates mesenteric adipocyte poor differentiation to alleviate Crohn's disease ‐like colitis via the Axin2/GSK3β pathway. Issue 10 (16th June 2022) - Li, Jing; Zuo, Lugen; Geng, Zhijun; Li, Qingqing; Cheng, Yang; Yang, Zi; Shi, Ruohan; Zhou, Yueqing; Nie, Wenhu; Wang, Yueyue; Zhang, Xiaofeng; Ge, Sitang; et al.
Abstract: Objectives: Crohn's disease (CD) mesenteric adipose tissue (MAT) inflammation affects enteritis through the interaction between the mesentery and intestine, and we previously found that poorly differentiated mesenteric adipocytes were related to its inflammatory features. Pygopus2 (Pygo2) is a key negative regulator of adipocyte differentiation. We aimed to determine whether Pygo2 participates in CD mesenteric lesions and whether Pygo2 knockdown would be beneficial in a CD model ( Il‐10 −/− mice). Methods: Pygo2 expression in MAT from control and CD patients and Il‐10 −/− mice was measured by immunohistochemistry. Lentiviral transfection was used to regulate Pygo2 expression in Il‐10 −/− mice, and the effects on mesenteric adipocyte differentiation, inflammation, and dysfunction during spontaneous colitis, as well as the possible mechanism, were investigated. Results: Pygo2 expression was increased in MAT from CD patients and Il‐10 −/− mice, and its expression correlated with poor adipocyte differentiation and inflammation. Pygo2 knockdown significantly ameliorated colitis in Il‐10 −/− mice. Moreover, the downregulation of Pygo2 gene expression could promote adipocyte differentiation and inhibit adipocyte inflammation in vivo and in vitro, and the effects were at least partly mediated by the Axis inhibition protein 2 (Axin2)/glycogen synthase kinase 3 beta (GSK3β) pathway. Conclusions: The increase in Pygo2 may be related to mesenteric adipocyte poor differentiation and inflammatory features of CD, and Pygo2 inhibition could alleviate CD‐like colitis by improving mesenteric lesions by regulating the Axin2/GSK3β pathway. Abstract : The increase in Pygopus2 (Pygo2) may be related to mesenteric adipocyte poor differentiation and inflammatory features of CD, and Pygo2 inhibition could alleviate adipocyte differentiation and mesenteric lesions by regulating the Axin2/GSK3β pathway.